Rainwater Catchment Reservoir To Support The Development of Community-Based Sustainable Ecotourism In Sumberkima Village Forest In The North of Bali-Indonesia - Putu Indah Rahmawati; I Ketut Sudiana; Ni Made Ary Widiastini (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Sumberkima Village is one of the villages in Buleleng Regency in the north of Bali island. This village has extensive forest land. Despite having huge area of forests, Sumberkima Village still struggles with poverty, unemployment, and a low level of education. Sumberkima Village also has significant disaster potential, particularly droughts during the dry season, and the village has previously experienced fires due to extreme dryness. This disaster occurs in accordance with predictions regarding the impacts of climate change, which indicate that several areas will experience significant adverse effects due to climate change. In addition to climate change, the summer drought that exacerbates the water crisis in Bali is also attributed to water usage by the tourism sector. This Community Service aims to create a mini reservoir to improve the economy and tourism in Sumberkima Village. The implemented community service program involves the application of simple water harvesting technology and empowers village communities through tree planting initiatives.